Toward participatory decision-making in river corridor management: two case studies from the European Alps. Issue 7 (7th June 2018) - Mazzorana, B.; Nardini, A.; Comiti, F.; Vignoli, G.; Cook, E.; Ulloa, H.; Iroumé, A.
Abstract : River managers are aware that river restoration entails addressing and effectively solving wicked social-ecological problems. Contemporary river corridor management is characterized by a variety of actors with different perspectives and interests, and by complex institutional settings and legal landscapes. Additionally, at the intersection between litho-, hydro-, and biological fields, new research suggests that river restoration should reactivate matter and energy fluxes, re-establish spatial connections with the floodplains, and enhance aquatic and terrestrial habitats without exacerbating flood risk. First, we outline a general structure of participatory river corridor management that addresses the following key requirements: (1) unambiguous, participatory spatial delineation of the river corridor; (2) comprehensive assessment of the river corridor's hydro-geomorphological, ecological, socio-economic and cultural processes; (3) transparency and consistency of the decision-making process; as well as (4) a coherent envisioning process. Subsequently, we present an overview of two river corridor management processes, conducted in South Tyrol, Italy. Specifically, we analysed the Etsch/Adige River corridor between Laas/Lasa and Glurns/Glorenza in the Upper Vinschgau/Venosta valley characterized by intense agricultural land use and the densely populated Eisack/Isarco River corridor in Brixen/Bressanone. Based on structured interviews with project managers, we highlight strengths and shortcomings of the proposed participatory management and envisage procedural improvements.